WNK1 activates SGK1 to regulate the epithelial sodium channel - Xu, Bing-e (National Academy of Sciences, 2005)
WNK (with no lysine [K]) kinases are serine-threonine protein kinases with an atypical placement of the catalytic lysine. Intronic deletions increase the expression of WNK1 in humans and cause pseudohypoaldosteronism type II, a form of hypertension. WNKs have been linked to ion carriers, but the underlying regulatory mechanisms are unknown. Here, we report a mechanism for the control of ion permeability by WNK1. We show that WNK1 activates the serum- and glucocorticoid-inducible protein kinase SGK1, leading to activation of the epithelial sodium channel. Increased channel activity induced by WNK1 depends on SGK1 and the E3 ubiquitin ligase Nedd4-2. This finding provides compelling evidence that this molecular mechanism contributes to the pathogenesis of hypertension in pseudohypoaldosteronism type II caused by WNK1 and, possibly, in other forms of hypertension.